TEACHER BURNOUT IN THE DIGITAL TRANSITION: IMPLICATIONS FOR LEARNING QUALITY - Dhayinta, Shellya Tanaya; Nasir, Mohammad; Zulfaida, Arini (Four Son Scholarship, 2025)
Digital transformation in the world of Education has accelerated the change in the teaching-learning paradigm, especially after the COVID-19 pandemic. Teachers now not only act as teachers but also as digital facilitators who must master various technology platforms and online learning media. However, this transition brings challenges in the form of burnout experienced by teachers, mainly due to the imbalance between high job demands and limited resources. This study aims to understand the experience of teacher burnout in the digital transition period, the factors that cause it, and its implications for the quality of learning. Using a qualitative approach with phenomenological design, this study involved 15 teachers from secondary schools who actively implemented online and hybrid learning. The main findings suggest that emotional burnout, which is the first dimension of burnout, causes teachers to feel depressed and demotivated. This fatigue then leads to depersonalization, in which the teacher feels separated from the students and focuses more on administrative tasks than on building personal relationships. The main contributing factors to this burnout are technological demands, the digital administrative burden, as well as the lack of adequate technical support and training. The impact of burnout affects the decline in teaching motivation, the quality of teacher-student interaction, and creativity in learning. The study suggests that educational institutions should provide better technical support, continuous digital training, as well as policies to reduce the administrative burden for teachers so that the quality of learning can be maintained in the digital age